Human Rights, Stigma, and Substance Use - Jenifer Wogen; Maria Teresa Restrepo (Harvard FXB Center for Health and Human Rights, 2020)
The primary purpose of political, civil, socioeconomic, and cultural rights is to protect the dignity of all human beings. Good mental health and well-being is defined by the "social, psychosocial, economic, and physical environment that enables individuals and populations to live a life of dignity, with full enjoyment of their rights and in the equitable pursuit of their potential." Stigmatization, discrimination, and negative stereotypes are barriers to mental health and well-being. Individuals with mental health problems, including those with drug dependence, suffer stigmatization, which is a direct affront to dignity and may have enduring health impacts. This paper discusses the implications of stigma for a human-rights based approach to improving mental health among those with drug dependence, with a focus on the opioid epidemic now ravaging the United States. It explores the public health burden of stigma related to substance misuse, including stigma in the context of treatment and health care. It also discusses the role of policy initiatives-including decriminalization-in addressing stigma related to substance misuse.